Social solidarity, human rights and Roma: unequal access to basic resources in Central and Eastern Europe - Filčák, Richard (Reinventing Social Solidarity across Europe, 2011)
IntroductionInhabitants regularly, especially in the summer time, suffer from lack of water and they usually travel to the cooperative farm for water, carrying it back to their houses. This is labor usually performed by women and children. They often take water from streams in the forest, which is of doubtful quality, especially after the rains when the streams contain mud and the water is of yellow or brown color. (Filčák, 2007)The continuing presence of unequal access to basic resources and widespread socio-economic inequalities in Europe works against the achievement of social solidarity and integration across European societies (Bulpett, 2002; Madanipour et al, 2005; Filčák, 2007). Conversely, it may also be argued that the displacement of ‘social solidarity’ in favour of ‘democracy’ within European integrationist discourse has contributed to the partial eclipse of human rights approaches focusing on ‘equality’ and ‘social inclusion’ within public policy rationales. Previous work has clearly revealed linkages between social inequality and exclusion, and social integration (Barry, 1998; Popay et al, 2006). The examination of social solidarity implies studying processes of integration, or the degree and types of social interactions present within society.In this chapter, attention is focused on governmental actions influencing living conditions and social differences within society. There are several ways in which governments can influence social differences, cohesion, inequalities and relational levels of social solidarity in society. It can be done via economic policies (such as capital accumulation, investments), fiscal policies (such as taxation) and public policies (such as social and welfare policies), or via the building of legal frameworks such as anti-discrimination policies. For the sake of clear argument, in what follows we abstract from an analysis of the general economic and fiscal attributes of the functioning of society and their link with cohesion or inequalities, and focus our attention on public policies and the way they influence the integration or division of society. We assume that public, especially social, policies in any country may tend to be either residual or universalistic. In reality, the situation is always a mix of these ideal types because, in order to gain support among the broad public that is targeted, social policies are often based on a universal system of social protection (CoE, 2001).